Towards a cultural history of digital autodidacticism: changing cultural narratives of education - Julian Sefton-Green (Perspectiva)
The essay argues that the various new imaginaries of the connected, creative, autonomous, coding, motivated and making digital learner have their roots in diverse and older visions of a different kind education system (especially the craft learner working in communities of practice) than that promulgated by the human-capital inspired neoliberal governmentalised States in the world today. Tracing the histories of the older imaginaries in a cultural history of autodidacticism I examine how they become incorporated by, and thus recalibrate competing visions of the “new learner of tomorrow”.